Sexual size dimorphism in anurans fails to obey Rensch’s rule - Liao, Wen Bo (BioMed Central, 2013)
BACKGROUND: Sexual size dimorphism (SSD) is related to ecology, behaviour and life history of organisms. Rensch’s rule states that SSD increases with overall body size in species where males are the larger sex, while decreasing with body size when females are larger. To test this rule, we analysed literature as well as own data on male and female body size in anurans (39 species and 17 genera). We also tested the hypothesis that SSD is largely a function of age difference between the sexes. RESULTS: Our data set encompassed 36 species with female-biased SSD, and three species with male-biased SSD. All considered species failed to support Rensch’s rule, also when the analyses were phylogenetically corrected. However, SSD was significantly correlated with Sexual Age Difference (SAD) across species. We also found a significant correlation between SSD contrasts and SAD contrasts. CONCLUSIONS: Our study suggests that Rensch’s rule does not accurately describe macroevolutionary patterns of SSD in anurans. That SAD can explain most of the variation in SSD among species when controlling for phylogenetic effects suggests that phylogeny is not responsible for the broad relationship between age and size across the sexes.